Dampak Perubahan Iklim Terhadap Usahatani dan Keberlanjutan Pangan di Desa Reban Kecamatan Reban Kabupaten Batang - Salsabila, Zelvia; Rohmah, Farida; Arisandi, Devy (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
crop failure. Farmers' understanding of how to deal with climate change is necessary because the agricultural sector is highly dependent on and vulnerable to climate change. As a result, agriculture and climate change are closely intertwined. The purpose of this study is to evaluate farmers' level of awareness of current climate change and its impacts, especially on food crops. This research used descriptive qualitative research methods with data collection methods in the form of primary and secondary data. Primary data was taken from interviews with the community and observations at the research site. And for secondary data obtained from the BMKG website page and Kompas.id. Descriptive analysis is used in the data analysis plan. The research findings show that both farmers who failed to harvest and those who succeeded in harvesting have known and felt the changes that occurred, such as changes in the growing season, changes in temperature, changes in rainfall, extreme weather and pest attacks. However, farmers are still unable to define what climate change is. Farmers endure lower yields, more pest attacks, higher probability of crop failure, and lower farmer income as a result of climate change, among other impacts. Farmers who experience crop failure usually resort to the following three ways first, borrowing money from friends, family, or neighbors second, doing side jobs such as being a construction worker, farm laborer on a neighbor's farm, or being a motorcycle taxi driver and third, using savings from the previous harvest.